Resuscitation with Hydroxyethyl Starch Maintains Hemodynamic Coherence in Ovine Hemorrhagic Shock. (January 2020) - Arnemann, Philip-Helge; Hessler, Michael; Kampmeier, Tim; Seidel, Laura; Malek, Youssef; Van Aken, Hugo; Morelli, Andrea; Rehberg, Sebastian; Ince, Can; Ertmer, Christian
Abstract : Background: Fluid resuscitation in hemorrhagic shock aims to restore hemodynamics and repair altered microcirculation. Hemodynamic coherence is the concordant performance of macro- and microcirculation. The present study on fluid therapy in hemorrhagic shock hypothesized that the choice of fluid (0.9% sodium chloride [saline group] or balanced 6% hydroxyethyl starch 130/0.4 [hydroxyethyl starch group]) impacts on hemodynamic coherence. Methods: After instrumentation, 10 sheep were bled up to 30 ml/kg body weight of blood stopping at a mean arterial pressure of 30 mmHg to establish hemorrhagic shock. To reestablish baseline mean arterial pressure, they received either saline or hydroxyethyl starch (each n = 5). Hemodynamic coherence was assessed by comparison of changes in mean arterial pressure and both perfused vessel density and microvascular flow index. Results: Bleeding of 23 ml/kg blood [21; 30] (median [25th; 75th percentile]) in the saline group and 24 ml/kg [22; 25] ( P = 0.916) in the hydroxyethyl starch group led to hemorrhagic shock. Fluid resuscitation reestablished baseline mean arterial pressure in all sheep of the hydroxyethyl starch group and in one sheep of the saline group. In the saline group 4, 980 ml [3, 312; 5, 700] and in the hydroxyethyl starch group 610 ml [489; 615] of fluid were needed ( P = 0.009). In hemorrhagic shock perfused vessel density (saline from 100% to 83% [49; 86]; hydroxyethyl starch from 100% to 74% [61; 80]) and microvascular flow index (saline from 3.1 [2.5; 3.3] to 2.0 [1.6; 2.3]; hydroxyethyl starch from 2.9 [2.9; 3.1] to 2.5 [2.3; 2.7]) decreased in both groups. After resuscitation both variables improved in the hydroxyethyl starch group (perfused vessel density: 125% [120; 147]; microvascular flow index: 3.4 [3.2; 3.5]), whereas in the saline group perfused vessel density further decreased (64% [62; 79]) and microvascular flow index increased less than in the hydroxyethyl starch group (2.7 [2.4; 2.8]; both P < 0.001 for saline vs. hydroxyethyl starch). Conclusions: Resuscitation with hydroxyethyl starch maintained coherence in hemorrhagic shock. In contrast, saline only improved macro- but not microcirculation. Hemodynamic coherence might be influenced by the choice of resuscitation fluid. Abstract : In a sheep model of hemorrhagic shock, resuscitation with both saline and hydroxyethyl starch restored mean arterial pressure (macrocirculation). After fluid resuscitation with hydroxyethyl starch, microcirculatory perfused vessel density and microvascular flow index (microcirculation) both improved, while saline only marginally improved microvascular flow index and perfused vessel density decreased further. Resuscitation with hydroxyethyl starch but not saline maintained hemodynamic coherence after hemorrhagic shock.Supplemental Digital Content is available in the text.